2003
DOI: 10.1095/biolreprod.102.005777
|View full text |Cite
|
Sign up to set email alerts
|

Zona Pellucida Induces Activation of Phospholipase A2 During Acrosomal Exocytosis in Guinea Pig Spermatozoa1

Abstract: Phospholipase A(2) (PLA(2)) is activated in spermatozoa in response to progesterone and Ca(2+) ionophores, but to our knowledge, no study has yet reported zona pellucida (ZP)-induced activation of PLA(2). We investigated whether PLA(2) is involved in ZP-stimulated acrosomal exocytosis, if Ca(2+) is required for activation of PLA(2), and signal transduction pathways modulating PLA(2) using guinea pig sperm as a model. Spermatozoa were capacitated and labeled in low-Ca(2+) medium with [(14)C]choline chloride or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…Like its analog SGC, SGG may be cytotoxic when present intracellularly at aberrantly high levels ( 16 ). Because Sertoli cells and male germ cells contain lipases (38)(39)(40), lyso-SGG may be produced following the intracellular accumulation of SGG in Arsa Ϫ / Ϫ testes. Lysoglycolipids are believed to be more cytotoxic than the parental lipids ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like its analog SGC, SGG may be cytotoxic when present intracellularly at aberrantly high levels ( 16 ). Because Sertoli cells and male germ cells contain lipases (38)(39)(40), lyso-SGG may be produced following the intracellular accumulation of SGG in Arsa Ϫ / Ϫ testes. Lysoglycolipids are believed to be more cytotoxic than the parental lipids ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2ϩ signaling in the tail of spermatozoa is involved in regulating flagellar motion, and [Ca 2ϩ ] in the head of spermatozoa is involved in the acrosomal reaction induced in spermatozoa by oocyte zona pellucida (45), a reaction in which iPLA 2 ␤ could participate. A PLA 2 is activated during induction of the acrosomal reaction by zona pellucida and releases arachidonic acid and LPC from spermatozoa membrane phospholipids (46). LPC also induces the acrosome reaction in spermatozoa (30,32), and one species of LPC (2-lysoplasmanylcholine) is the precursor of the platelet-activating factor, which is produced by spermatozoa and is an autocrine inducer of capacitation (47).…”
Section: Discussionmentioning
confidence: 99%
“…Analogous phenotype is exhibited in WT spermatozoa treated with BEL. Based on earlier reports of involvement of LPC in acrosome reaction (197)(198)(199) and induction of capacitation ( 200 ), it was suggested that LPC levels are decreased the rate of [ 3 H]AA incorporation into P388D1 cell PC ( 165,166 ).…”
Section: Proposed Roles For Ipla 2 ␤mentioning
confidence: 99%